EFEKTIFITAS KOMPRES DINGIN DAN HANGAT PADA PENATALEKSANAAN DEMAM - Nurlaili Susanti (SAINSTIS, 2011)
Fever is a symptom that accompanies some infectious and non infectious diseases. Fever cause metabolic consequences such as dehydration, increasing oxygen consumption and metabolic rate. Treatment of fever can reduce patient discomfort and another symptoms such as fatigue, myalgia, diaphoresis and chills.In addition to antipyretic, the use of physical methods to reduce fever has been widely applied. Physical methods of cooling are the treatment of choice for hyperthermia, but their value in the treatment of fever remains uncertain. Fever treated with tepid-water sponging and combined with antipyretic drugs are more effectively than those treated with antipyretic drugs alone. Tepid-water sponging represents a simple, nonsedating method to combat the metabolic impact of shivering and to induce cutaneous vasodilatation that increases heat loss.